The Formation Of Religious Characters Of Students Through Religion Activities - Rahma Nurbaiti; Susiati Alwy; Imam Taulabi (Institut Agama Islam Tribakti Kediri, 2020)
This study aims to find out how the religious character of students developed in the Madrasah Ibtidaiyah Negeri 2 Bandar Kidul and how the formation of character through habituation of religious activities. The type and approach of research use descriptive qualitative. Data sources were obtained through interviews with the headmaster of the madrasa, curriculum waka, religious waka, class teachers, Islamic Religious Education teachers, several student guardians, and students. The results showed that the religious character of the students developed was devotion, sincerity, honesty, politeness, help, help, love, grace, cleanliness, competition, and gratitude. Formation of religious character through the habituation of religious activities through joint prayer before and after learning, performing dhuha and dhuhur prayers, reading juz 'amma, asmaul husna, istighasah, infaq, habituation Salam, salim, greeting, smiling, polite and polite, religious extracurricular activities such as tambourines, recite the Qur'an, the commemoration of Islamic holidays. Religious character is formed through the habituation of religious activities. [Penelitian ini bertujuan mengetahui bagaimana karakter religius siswa yang dikembangkan di Madrasah Ibtidaiyah Negeri 2 Bandar Kidul dan bagaimana pembentukan karakter melalui pembiasaan aktivitas keagamaan. Jenis dan pendekatan penelitian menggunakan kualitatif deskriptif. Sumber data diperoleh melalui wawancara dengan kepala madrasah, waka kurikulum, waka keagamaan, guru kelas, guru Pendidikan Agama Islam, beberapa wali murid dan murid. Hasil penelitian menunjukkan bahwa karakter religius siswa yang dikembangkan yaitu ketaqwaan, keikhlasan, kejujuran, kesopanan, tolong-menolong, cinta rosul, kebersihan, kompetitif, dan rasa syukur. Pembentukan karakter religius melalui pembiasaan aktivitas keagamaan melalui doa bersama sebelum dan sesudah pembelajaran, pelaksanaan shalat dhuha dan dhuhur berjamaah, pembacaan juz ‘amma, asmaul husna, istighasah, infaq, pembiasaan Salam, salim, sapa, senyum, sopan dan santun, kegiatan ekstrakulikuler keagamaan seperti rebana, Baca Tulis Qur’an, Peringatan Hari Besar Islam. Karakter religius yang terbentuk melalui pembiasaan aktivitas keagamaan]